1963
DOI: 10.1126/science.142.3598.1477
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Intelligence: A Review

Abstract: A survey of the literature of the past 50 years reveals remarkable consistency in the accumulated data relating mental functioning to genetic potentials. Intragroup resemblance in intellectual abilities increases in proportion to the degree genetic relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
52
2

Year Published

1965
1965
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(60 citation statements)
references
References 4 publications
5
52
2
Order By: Relevance
“…This result contradicts previously published studies demonstrating parent-offspring resemblance on intelligence tests (Bouchard & McGue, 1981;Erlenmeyer-Kimling & Jarvik, 1963;Reed & Rich, 1982;van Leeuwen, van den Berg, & Boomsma, 2008). In these studies, moderate correlations (approximately .50) were measured.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…This result contradicts previously published studies demonstrating parent-offspring resemblance on intelligence tests (Bouchard & McGue, 1981;Erlenmeyer-Kimling & Jarvik, 1963;Reed & Rich, 1982;van Leeuwen, van den Berg, & Boomsma, 2008). In these studies, moderate correlations (approximately .50) were measured.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies have suggested that heritable intelligence can vary between 0.2 and 0.86. In other words, 20 to 86% of the phenotypic variance observed in measured cognitive abilities is attributed to genetic factors (Bouchard & McGue, 1981;Brouwer et al, 2014;Deary, Johnson, & Houlihan, 2009;Erlenmeyer-Kimling & Jarvik, 1963;Lynn & Hattori, 1990;Nisbett et al, 2012;Plomin & DeFries, 1980;Turkheimer, Haley, Waldron, D'Onofrio, & Gottesman, 2003). For instance, in a fundamental review that compared 111 studies worldwide, investigating familial IQ correlations (Bouchard & McGue, 1981), the authors suggested an association of .86 for monozygotic (MZ) twins raised together and .72 for monozygotic twins raised separately.…”
mentioning
confidence: 99%
See 3 more Smart Citations